Perbandingan Nilai Daya Luaran Panel Surya Kapasitas 50Wp Terhadap Posisi Reflektor Cermin Datar - Sumardiono, Arif; Hazrina, Fadhillah; Syaefulloh, Arief (Infotekmesin, 2023)
Solar panel systems are widely used to meet energy needs at this time. Solar panels have optimal power for 4 hours, namely 10:00 to 14:00. but this is still said to be not optimal if the angle of the static solar panels does not follow the movement of the sun. This can also be caused by weather factors that are covered in clouds. Previous research conducted by Tri Wahyu Ardianto used mirror reflectors but was not equipped with sensors and data storage. Based on this, to optimize solar panel energy, a flat mirror reflector design for solar panels has been made, equipped with four flat mirror reflectors on each side to form a large square. The solar panel is placed in the middle between the four flat mirrors. In this study, the measurement of electric power was carried out by carrying 3 variable angles for reflector positions, namely 0°, 60°, and 70°. The decision of the three reflector positions is made to find out the ratio of the maximum output power values. This system is also equipped with current, voltage, and light intensity sensors. The results show that the maximum output power of solar panels is shown at the reflector position of 60° with an average power output of 19.70 Watt followed by a reflector position of 70° with an average output power of 19.18 Watt and finally the reflector position is 0° with an average output power value of 14.87 Watt.